Performance-based aid, enhanced advising, and the income gap in college graduation: Evidence from a randomized controlled trial - Christopher Erwin; Melissa Binder; Cynthia Miller; Kate Krause (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2020)
Income gaps in college enrollment, persistence, and graduation raise concerns for those interested in equal opportunity in higher education. We present findings from a randomly assigned scholarship for low-income students at a medium-sized public four-year university. The program focused solely on the first four semesters of enrollment and tied aid disbursements to modest academic benchmarks and enhanced academic advising. Meaningful decreases in time to degree appear to be driven by students with the lowest academic preparation and family income. Treated students took out approximately 20 percent less in student loans during the duration of the program. Participants also indicated high satisfaction with the program's model of enhanced academic advising.
Keywords: 330; enhanced advising; merit-based financial aid; income gaps; college graduation